Smoking Effects in Foot and Ankle Surgery: An Evidence-Based Review. (October 2019) - Beahrs, Taylor R.; Reagan, James; Bettin, Clayton C.; Grear, Benjamin J.; Murphy, G. Andrew; Richardson, David R.
Background: The purpose of this article was to review the basic science pertaining to the harmful effects of cigarette smoke, summarize recent clinical outcome studies, and examine the benefits of smoking cessation and the efficacy of current smoking cessation strategies. Methods: The literature concerning basic science, clinical outcomes, and smoking cessation was reviewed; over half (56%) of the 52 articles reviewed were published in the last 5 years. Results: Smoking is associated with low bone mineral density, delayed fracture union, peri-implant bone loss, and implant failure. Orthopedic surgical patients who smoke have increased pain and lower overall patient satisfaction, along with significantly increased rates of wound healing complications. Discussion/Conclusion: Active smoking is a significant modifiable risk factor and should be discontinued before foot and ankle surgery whenever possible. Orthopedic surgeons play an important role in educating patients on the effects of smoking and facilitating access to smoking cessation resources. Level of Evidence: Level V, expert opinion.